Injuries and violence: a global public health challenge (Italian Journal of Public Health, 2010)
Injuries and violence are a significant cause of mortality and physical disability. Injuries killed five million people worldwide each year [1]. The level of this dilemma, however, differs significantly by age, sex, region and economic development [2]. Globally, road traffic injury mortalities, self-inflicted injury mortality and interpersonal violence, war, drowning, and exposure to fire are the leading cause of deaths among people aged 15-44 years [3]. This special issue aims to assess the magnitude of this problem, identify risk factors and explore prevention strategies to alleviate the burden of injuries and violence. There is a dire need to increase the knowledge of the extent of problem, and associated risk factors that needs to be targeted for prevention. Erosa et al., examined reports of verbal and physical abuse from family caregivers of adults with severe physical, neurological and developmental disabilities, and found that caregivers who reported some form of abuse reported significantly greater distress and burden than caregivers who did not report any abuse. Grice et al., found that reported histories of work-related physical assault and work-related threat were associated with elevated risks of current work-related physical assault. Ahmad, systematically reviewed and summarized current scientific knowledge on the use of interactive computer-assisted screening to detect intimate partner violence (IPV).